2019
DOI: 10.1101/788653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific phenotypic effects and evolutionary history of an ancient polymorphic deletion of the human growth hormone receptor

Abstract: The deletion of the third exon of the growth hormone receptor ( GHRd3 ) is one of the most common genomic structural variants in the human genome. This deletion has been linked to response to growth hormone, placenta size, birth weight, growth after birth, time of menarche, adult height, and longevity. However, its evolutionary history and the exact mechanisms through which it affects phenotypes remain unresolved. While the analysis of thousands of genomes suggests that this deletion was nearly fixed in the an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…This is consistent with our locus-specific analyses of ancient deletion polymorphisms. For example, we recently reported that the deletion of the third exon of the human growth hormone receptor gene (GHR) has evolved under temporally and geographically variable adaptive constraints (Saitou, Resendez, et al, 2021). These ancient deletions are common and old, and also exhibit high population differentiation.…”
Section: Functional Ancient Deletions Are Likely Targets Of Balancing...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with our locus-specific analyses of ancient deletion polymorphisms. For example, we recently reported that the deletion of the third exon of the human growth hormone receptor gene (GHR) has evolved under temporally and geographically variable adaptive constraints (Saitou, Resendez, et al, 2021). These ancient deletions are common and old, and also exhibit high population differentiation.…”
Section: Functional Ancient Deletions Are Likely Targets Of Balancing...mentioning
confidence: 99%
“…Using the GTeX database, we found at least four other instances where ancient deletions lead to the expression of different isoforms, including deletions affecting the HLA-DRB1-6, HLA-DOB, SIRPB1, GHR and CYP3A43 genes. We recently showed that the ancient deletion of the third exon of the growth hormone receptor gene leads to the expression of a smaller version of growth hormone, which may be adaptive in times of starvation (Saitou, Resendez, et al, 2021). The SIRPB1 gene encodes a glycosylated transmembrane receptor protein (Kharitonenkov et al, 1997) and its different isoforms may lead to the recognition of different pathogens.…”
Section: Functional Ancient Deletions Are Related To Immune and Metab...mentioning
confidence: 99%
“…When it comes to investigating the impact of ancient hominin introgression on phenotypic variation, the challenge is more general. The relationships between a genetic variant and phenotype are not straightforward; they are dependent on both genomic and environmental backgrounds (e.g., Resendez et al, ). However, there are increasing numbers of databases involving millions of participants, as well as concurrent mechanistic studies involving modified cell lines and model organisms (Visscher et al, ).…”
Section: An Exciting Tomorrow and A Whole Lot Of Gaps To Fillmentioning
confidence: 99%
“…S4F) suggest that this common GHR variant attenuates hepatic BCL6 function. Further, the ability of the GHRd3 variant to stave off nutritional stress (22), coupled with our study, implies that the GH-BCL6 signaling axis creates a trade-off for females that diminishes fitness during infection while enhancing survival in the fasted state. Indeed, in most recorded famines, survival rates for women outpace men (23).…”
mentioning
confidence: 57%
“…To extend these findings, we leveraged a mouse model carrying the common human variant of Growth Hormone Receptor (GHRd3, deletion of exon 3) that mimics increased GH signaling. This variant feminizes livers in male mice and is thought to confer an evolutionary advantage during periods of food scarcity in humans (22). The significant overlap in hepatic gene changes detected in Ghrd3 and Bcl6A lbCre mutant males and the trend towards lowered Bcl6 in Ghrd3 male livers (Fig.…”
mentioning
confidence: 99%